Accumulation of Heavy Metal Copper (Cu) in Mangrove Vegetation in River Flow of the Sea Coast - Dina Riska Triswanti; Moch Arifin; Purnomo Edi Sasongko (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Mangroves have ecological functions, one of which is being able to absorb and accumulate heavy metals which can pollute the environment. The aim of the research is to assess the ability of mangroves to accumulate the heavy metal Cu. The research location is on the East Surabaya River Coast. The research method is purposive sampling with a distance of 250 m from one point to another. The pH value is classified as neutral to slightly alkaline. The salinity value is classified as very high. The texture of mangrove sediments has fine particles consisting of clay and dust. Cu concentrations in sediments are still below quality standards according to the United States Environmental Protection Agency (US-EPA). The Cu concentration in the sediment was highest in the Tambak Oso River with an average of 50.50 mg/kg. The concentration of heavy metals in the roots is higher than in the leaves. The bioconcentration factor (BCF) value is classified as the excluder, while the translocation factor value is classified as the phytostabilization and phytoextraction classes. Keywords: Estuaries, Mangroves, Pollution, East surabaya, Cu toxicity.